International Financial Statistics, March 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This March issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. Balance-of-Payments Statistics Yearbook contains two sections; World and Regional Tables, and Country Tables. The first section presents 21 world and regional tables for major components of the balance of payments, net International Investment Position (IIP), and total financial assets and total liabilities for the IIP. The second section provides detailed tables on balance-of-payments statistics for 189 economies and IIP data for 143 economies. IFS, Balance-of-Payments Statistics, Direction of Trade Statistics, and Government Finance Statistics are available on CD-ROM by annual subscription. The CD-ROMs incorporate a Windows-based browser facility, as well as a flat file of the database in scientific notation. The Statistics Department of the IMF is pleased to make available to users the IFS, Balance-of-Payments Statistics, Direction of Trade Statistics, and Government Finance Statistics databases through the new, easy-to-use data.IMF.org online service. New features include Data Portals, which provide quick access to predefined tables, maps, graphs, and charts aimed at visualizing many common data searches.